Artificial intelligence and achieving environmental sustainability in controlling agricultural pests (Journal of the College of Basic Education, 2025)
Agricultural sustainability is about providing basic human needs for food and clothing and improving the resource base to support agriculture and meet future generations' needs without depletion or degradation. Artificial intelligence in agriculture enhances sustainability and resilience by improving the use of environmental management resources. It enables farmers to use artificial intelligence applications to monitor field inputs of water, fertilizers, and chemical pesticides, allowing for adjustments to more sustainable operations. It also enables early identification of A Agricultural pests and diseases and the application of chemical pesticides to target agricultural pests, thus reducing pesticide consumption. Artificial intelligence in agriculture provides early and rapid identification of agricultural pests, which leads to preserving crops and preventing damage and loss of production. Artificial intelligence uses image recognition technology to scan images of crops for signs of agricultural pests or diseases. This helps farmers take proactive steps in pest control. It also diagnoses plant abnormalities using modern sensors and continuous monitoring, enabling farmers to respond to pest control efforts and ensure healthier, more productive crops